A study on the process of literacy and literacy, together with the students of the 6th grade of elementary school II in a state school of Manaus (Research, Society and Development, 2022)
Learning the spelling of letters requires the child the ability and readiness to decipher isolated phonemes from the words he knows as a whole, that is, fragments of the word. Thus, the general objective of the research is to characterize the main obstacles present in the process of literacy and literacy of elementary school II students.  This research was carried out in the morning shift, during the supervised internship period, with teachers, parents and elementary school students.  In the study, it was also observed inside the classroom that contained 21 students being autistic, the teacher worked alone without any help. Data analysis under the qualitative approach was presented descriptively focusing on the interviewees' point of view. The work of information collection, and the consequent analysis of data.  Thus, each child, when entering the school universe in order to learn to read and write, brings with him a whole trajectory of contacts with written language that the school given its need for control of teaching, ends up not taking into account, which can be harmful during the process of literary production. Based on this thought, it is pointed out that nowadays, it is in elementary school that the teacher is compared to children and adolescents who have their own interests in their development, which already characterize their physical, emotional, social and cognitive aspects, precisely by the interaction with those who surround them in their life from birth and this reflects in the teaching work.